A Living Will - Cruz-Lucero, Rosario (Review of Women's Studies, 2023)
The short story, "A Living Will", is a commemoration of the centennials of both migrant labor in the Hawai'i plantations and the forced exile of lepers to Culion Island under the American public health system in the 1920s. These two grand historical narratives are encapsulated in the love story of an elderly couple who are reunited through the efforts of a nurse. The story also covers the topics of the OCW phenomenon, the mushrooming of nursing homes, and the emotional penance that elderly persons carry in their psyche after having lived a life of choices. Although the plotline centers on the nurse's search for Ernesto, the inner story is about the nurse, who, no matter how pure her intention, inexorably triggers a process that may expose Ernesto as a fraud. When we commit ourselves to action, we unintentionally set off a chain of events whose end, for all the purity of our intentions, we cannot determine. This is the human condition that is revealed in Nurse Garcia's confrontation with her well-meaning but accidentally evil self in "A Living Will".